„Catch the dream for all night”. Characteristic of the advertisements in the medical journals - Drozd, Barbara (Linguistic creativity in marketing, 2022)
The aim of the article was to analysed the advertisements derived from the medical journal „Medycyna po Dyplomie, which is addressed to specialised type of recipients, it means: doctor or doctor which is a specialist, and also adept (student). It was relevant to investigate if this kind of medicine advertisements stand out from the other well know television advertisements. The characteristics of the advertisement show that their recipients are strictly determined by specialised knowledge, specialised terms and acronims.